MODELING OF SCIENTIFIC AND TECHNICAL PROGRESS - Michael E. Mazurov (Статистика и экономика, 2016)
Scientific and technical progress can be represented in the form of an active medium in which they are earned achievements of the company. For modeling scientific and technological progress used standard mathematical models of self-organization, is solved by the method of scanning. In the computational experiment showed that the presence of the discoveries greatly accelerates the pace of scientific and technological progress.